1983
DOI: 10.1007/bf00376846
|View full text |Cite
|
Sign up to set email alerts
|

An antifungal terpenoid defends a neotropical tree (Hymenaea) against attack by fungus-growing ants (Atta)

Abstract: Foragers of the leafcutting ant, Atta cephalotes L. (Formicidae, Attini) seldom or never attack many of the plant species available to them in nature. In the semideciduous forests of lowland Guanacaste Province, Costa Rica, one of the tree species seldom cut is Hymenaea courbaril L. (Leguminosae, Caesalpinioideae). We tested the hypothesis that this species is avoided by the ants because of the presence of ant-repellent secondary compounds in the leaves. A bioassay to test repellency of leaf extracts was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 10 publications
0
53
0
2
Order By: Relevance
“…Owolabi et al (2013) reported in vitro cytotoxicity activity of (E)-b-caryophellene, caryophyllene oxide and a-humulene obtained from A. muricana leaf oil against MCF-7 cells with LC 50 values of 38.8, 23.0 and 22.1 lg/mL. Also, the role of (E)-b-caryophellene has been demonstrated in flora defence against pathogens and repellent activities against leaf-cutting ants and termites (Hubbell et al 1983;Messer et al 1990;Huang et al 2012). The fresh leaves oils (LC 50 ¼ 0.01 lg/mL) showed more potency than the standardized pesticidal extracts obtained from small twigs of pawpaw tree (LC 50 ¼ 0.04 lg/mL) reported by McLaughlin and Rogers (1998).…”
Section: Discussionmentioning
confidence: 99%
“…Owolabi et al (2013) reported in vitro cytotoxicity activity of (E)-b-caryophellene, caryophyllene oxide and a-humulene obtained from A. muricana leaf oil against MCF-7 cells with LC 50 values of 38.8, 23.0 and 22.1 lg/mL. Also, the role of (E)-b-caryophellene has been demonstrated in flora defence against pathogens and repellent activities against leaf-cutting ants and termites (Hubbell et al 1983;Messer et al 1990;Huang et al 2012). The fresh leaves oils (LC 50 ¼ 0.01 lg/mL) showed more potency than the standardized pesticidal extracts obtained from small twigs of pawpaw tree (LC 50 ¼ 0.04 lg/mL) reported by McLaughlin and Rogers (1998).…”
Section: Discussionmentioning
confidence: 99%
“…Repellency of the epoxide was 20 times greater than that of caryophyllene, its sesquiterpene hydrocarbon precursor. Caryophyllene epoxide was also tested for antifungal activity and found to be an extremely potent compound against many fungi (Hubbell et al 1983). …”
Section: Some Ecological Functions Of Volatile Fungal Sesquiterpenesmentioning
confidence: 99%
“…Leaf-cutting ant foraging is complex and a variety of factors other than endophyte content have also been found to influence the foraging preferences of leaf-cutting ants including: leaf toughness (Nichols-Orians and Schultz 1989), secondary compounds (Hubbell et al 1983, Howard 1988, nutrient content (Berish 1986, Howard 1988, Farji-Brener 2001, and epiphylls (Mueller and Wolf-Mueller 1991). To further complicate the matter, many of these variables in leaf tissue are covariates.…”
Section: Discussionmentioning
confidence: 99%